Kết tinh phân đoạn axit béo không no nhiều nối đôi từ dầu cá trích và cá basa - Hương, Lại Mai (Vietnam Journal of Chemistry, 2014)
Low temperature fractionation was employed to obtain polyunsaturated fatty acid (PUFA) concentrates from sardine and catfish oils. Different solutions of free fatty acids (FFAs) at various FFAs: solvent ratio (w/v) from these two oils were crystallized at -20oC and -70oC, respectively, using hexane and acetone as solvents. At the best crystallization condition, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) purities were reached 14.1% and 8.7% from sardine oil and linolenic acid (LA) purity was 31% from catfish oil.Keywords: Crystalline fraction, fish oil, polyunsaturated fatty acid, EPA, DHA, LA.